Fotografia jako medium poetyckiego doświadczenia miasta w wierszach Joanny Ziembińskiej-Kurek - Mirosława Szott (Annales Universitatis Paedagogicae Cracoviensis. Studia Poetica, 2014)
Photography as the medium of a poetic experience of the city in Joanna Ziembińska-Kurek’s output